Hungarian Monitoring, 17 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Events in the Gulf crisis - Genscher-Shevardnadze meeting - Soviet initiatives for foreign investors Domestic Affairs: - Hungarians stuck in Kuwait - Iraqi ambassador's press conference in Budapest - World Humanist Association conference - First prototype for new coat of arms finished Economy: - Land reprivatization - Trade talks with Cuba - Pre-agreement on the utilization of Óbuda island in the Danube - Government's housing policy Külpolitika: - Öbölválság eseményei - Genscher-Sevardnadze találkozó - Szovjet kedvezmények külföldi beruházóknak Belpolitika: - Kuvaitban rekedt magyarok - Iraki nagykövet sajtóértekezlete Budapesten - Humanista Világszervezet ülése - Elkészült az új címer első mintapéldánya Gazdaság: - Földek reprivatizációja - Kereskedelmi tárgyalások Kubával - Előszerződés az Óbudai-sziget hasznosításáról - A kormány lakáskoncepciója